Intrinsic metabolic depression in cells isolated from the hepatopancreas of estivating snails - Guppy, M; Reeves, D; Bishop, T; Withers, P; Buckingham, J; Brand, M (Federation of American Society of Experimental Biology (FASEB), 2000)
Many animals across the phylogenetic scale are routinely capable of depressing their metabolic rate to 5–15% of that at rest, remaining in this state sometimes for years. However, despite its widespread occurrence, the biochemical processes associated with metabolic depression remain obscure. We demonstrate here the development of an isolated cell model for the study of metabolic depression. The isolated cells from the hepatopancreas (digestive gland) of the land snail (Helix aspersa) are oxygen conformers; i.e., their rate of respiration depends on pO2. Cells isolated from estivating snails show a stable metabolic depression to 30% of control (despite the long and invasive process of cell isolation) when metabolic rate at the physiological pH and pO2 of the hemolymph of estivating snails is compared with metabolic rate at the physiological pH and pO2 of the hemolymph of control snails. When the extrinsic effects of pH and pO2 are excluded, the intrinsic metabolic depression of the cells from estivating snails is still to below 50% of control snails. The in vitro effect of pO2 on metabolic rate is independent of pH and state (awake or estivating), but the effects of pH and state significantly interact. This suggests that pH and state change affect metabolic depression by similar mechanisms but that the metabolic depression by hypoxia involves a separate mechanism.